Modified Almost Type Z-contraction: Pheerachate Bunpatcharacharoen, Sompob Saelee, Phachara Saipara - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we introduce the notion of Almost type Z-contraction and a new fixed point theorem in frame of metric spaces. We prove existence of fixed points for cyclic mappings. Also, we obtain fixed point results for weak contraction type mappings.